## Abstract

An ellipsometric technique based on angle-resolved light scattering is addressed to open applications in the field of imaging in random media. The first experimental demonstration is given to prove the selective extinction of different scattering sources such as surface roughness and bulk heterogeneity in optical components and liquids. The results are compared with theory.

© 2007 Optical Society of America

Full Article |

PDF Article

**OSA Recommended Articles**
### Equations (17)

Equations on this page are rendered with MathJax. Learn more.

(1)
$$\overrightarrow{E}={\overrightarrow{E}}_{1}+{\overrightarrow{E}}_{2}+{\overrightarrow{E}}_{12}$$
(2)
$$f(\overrightarrow{E},\theta )={E}_{s}\left(\theta \right)+\alpha \left(\theta \right){E}_{p}\left(\theta \right)$$
(3)
$$\alpha \left(\theta \right)=\mathrm{tan}\left[\psi \left(\theta \right)\right]\mathrm{exp}\left(j\left(\Delta \eta +\Delta {\eta}^{*}\left(\theta \right)\right)\right)$$
(4)
$$f(\overrightarrow{E},\theta )=0\phantom{\rule{.2em}{0ex}}\iff \phantom{\rule{.2em}{0ex}}\alpha \left(\theta \right)={\alpha}_{A}\left(\theta \right)=-\frac{{E}_{s}\left(\theta \right)}{{E}_{p}\left(\theta \right)}$$
(5)
$$\mathrm{tan}\left[\psi \left(\theta \right)\right]=\mid \frac{{E}_{s}\left(\theta \right)}{{E}_{p}\left(\theta \right)}\mid $$
(5)
$$\Delta {\eta}^{*}\left(\theta \right)=\pi -\left[\Delta \delta \left(\theta \right)+\Delta \eta \right]$$
(6)
$$\Delta \delta \left(\theta \right)={\delta}_{p}\left(\theta \right)-{\delta}_{s}\left(\theta \right)$$
(7)
$$f\left(\overrightarrow{E}\right)=f\left({\overrightarrow{E}}_{1}+{\overrightarrow{E}}_{2}+{\overrightarrow{E}}_{12}\right)=f\left({\overrightarrow{E}}_{1}\right)+f\left({\overrightarrow{E}}_{2}\right)+f\left({\overrightarrow{E}}_{12}\right)$$
(8)
$$f\left({\overrightarrow{E}}_{i}\right)={E}_{\mathrm{is}}\left(\theta \right)+\alpha \left(\theta \right){E}_{\mathrm{ip}}\left(\theta \right)\phantom{\rule{.5em}{0ex}}\mathrm{with}\phantom{\rule{.2em}{0ex}}i=1\phantom{\rule{.2em}{0ex}}\mathrm{or}\phantom{\rule{.2em}{0ex}}2$$
(8)
$$\phantom{\rule{.9em}{0ex}}\phantom{\rule{.9em}{0ex}}f\left({\overrightarrow{E}}_{12}\right)={E}_{12s}\left(\theta \right)+\alpha \left(\theta \right){E}_{12p}\left(\theta \right)$$
(9-a)
$$f\left({\overrightarrow{E}}_{i}\right)=0\phantom{\rule{.2em}{0ex}}\iff \phantom{\rule{.2em}{0ex}}{\alpha}_{\mathrm{iA}}\left(\theta \right)=-\frac{{E}_{\mathrm{is}}\left(\theta \right)}{{E}_{\mathrm{ip}}\left(\theta \right)}$$
(9-b)
$$f\left({\overrightarrow{E}}_{12}\right)=0\phantom{\rule{.2em}{0ex}}\iff \phantom{\rule{.2em}{0ex}}{\alpha}_{12A}\left(\theta \right)=-\frac{{E}_{12s}\left(\theta \right)}{{E}_{12p}\left(\theta \right)}$$
(10)
$$f\left(\overrightarrow{E}=\sum _{i=1}^{N}{\overrightarrow{E}}_{i}={\overrightarrow{E}}_{1\to N}\right)=\sum _{i=1}^{N}f\left({\overrightarrow{E}}_{i}\right)+f\left({\overrightarrow{E}}_{1-N}\right)$$
(11)
$$\mathrm{sin}{\theta}_{b}=\sqrt{\frac{{n}^{2}\left({n}^{2}-{\mathrm{sin}}^{2}i\right)}{{n}^{2}+\left({n}^{4}-1\right){\mathrm{sin}}^{2}i}}$$
(12)
$$f\left(\overrightarrow{E}\right)=f\left({\overrightarrow{E}}_{1}+{\overrightarrow{E}}_{2}+{\overrightarrow{E}}_{12}\right)=f\left({\overrightarrow{E}}_{1}\right)+f\left({\overrightarrow{E}}_{12}\right)$$
(13)
$$f\left(\overrightarrow{E}\right)=f\left({\overrightarrow{E}}_{1}+{\overrightarrow{E}}_{2}+{\overrightarrow{E}}_{12}\right)=f\left({\overrightarrow{E}}_{2}\right)+f\left({\overrightarrow{E}}_{12}\right)$$
(14)
$$f\left(\overrightarrow{E}\right)=f\left({\overrightarrow{E}}_{i}\right)\phantom{\rule{.5em}{0ex}}\iff \phantom{\rule{.5em}{0ex}}f\left({\overrightarrow{E}}_{j}+{\overrightarrow{E}}_{12}\right)=0$$